Cheese Price Softening in the U.S.: Determining Effects from Excessive Cheese in the Market - Wang, Zuyi; Tejeda, Hernan; Kim, Man-Keun; Siu, Wai Yan (Research on World Agricultural Economy, 2023)
The United States (U.S.) cheese sector has experienced continuous production and consumption growth since the 1990’s with its market characterized as having oligopolistic behavior, signaling that prices respond to supply. Despite the steady industry growth, it experienced a recent multi-year period of declining prices. This paper addresses how growth towards an all-time record surplus of cheese, in response to excess milk production and export drops, weakened U.S. cheese prices. This study finds there is a significant short-run effect on price from overly expanded cheese supply, i.e., specifically taking a 2019 monthly average supply of 2.48 billion pounds, a 10% rise in cheese supply results in an immediate price decrease of 8.7%, translating to an average decline of USD 0.15/pound. The cumulative effect on its price from this 10% change results in a cumulative drop in cheese prices of 18.9%, approximately equal to a decrease of USD 0.34/pound. Findings provide relevant information to cheese, dairy producers and stakeholders, for milk production schedules, risk management and dairy policy analysis.